Building the Islamic Character of Children through Extracurricular Programs at Islamic Elementary School, Gresik - widodo, Widodo; Shofwan, Imam; Lestari, Gunarti Dwi; Widyaswari, Monica (Islamic Research, 2025)
Abstract: The extracurricular program which is divided into several specializations shows the importance of supporting the development of Islamic character in schools. This cannot be denied, because character is a complex activity that involves family, community and the school environment. Extracurricular activities are learning activities held outside school hours as an addition or complement. Extracurricular programs are organized with the aim of developing students' potential, talents, interests, abilities, personality, cooperation and independence optimally. The aim of the research is to determine the role of extracurricular programs in building students' Islamic leadership character. School and extracurricular activities are a holistic unit and mutually influence a child's leadership character. The learning process occurs in both to create reliable human resources. In theory, learning is essentially an "individual process" which means that it occurs in humans uniquely. Qualitative research is descriptive. which describes completely and holistically the phenomena that occur. The research was conducted at the AL-Kayyis Gresik Integrative Islamic Elementary School with data collection techniques using in-depth interviews, participatory observation and document analysis. Meanwhile, qualitative research data analysis uses Miles & Huberman, namely; (1) data reduction, (2) data presentation, (3) drawing conclusions. Extracurricular programs can be recreational, achievement or life skills. Thus, there is a holistic and synergistic relationship between extracurricular activities and the cultivation of students' Islamic character. Keywords; Extracurrucular, Islamic Character, Children. Elementary school,